2023
DOI: 10.3390/jcm12103536
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Artificial Intelligence Assistance on the Radiologists’ Assessment of Lung Nodules on CT Scans: A Systematic Review

Abstract: To reduce the number of missed or misdiagnosed lung nodules on CT scans by radiologists, many Artificial Intelligence (AI) algorithms have been developed. Some algorithms are currently being implemented in clinical practice, but the question is whether radiologists and patients really benefit from the use of these novel tools. This study aimed to review how AI assistance for lung nodule assessment on CT scans affects the performances of radiologists. We searched for studies that evaluated radiologists’ perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Various studies have compared the performance of AI algorithms versus radiologists and highlighted higher sensitivity and FP rate when AI is used as a concurrent or second reader [ 26 29 ]. AI algorithms were found to have a mean number of FPs/scan ranging from 0.09 to 3.8 and a mean sensitivity (on a nodule basis) ranging from 0.54 to 0.96 [ 28 ]. In a study by Li et al [ 30 ], it was shown that deep learning algorithms not derived only from the LIDC-IDRI dataset [ 31 ] achieved good performance in nodule detection when tested on an external dataset, with sensitivity ranging from 0.75 to 1.00.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have compared the performance of AI algorithms versus radiologists and highlighted higher sensitivity and FP rate when AI is used as a concurrent or second reader [ 26 29 ]. AI algorithms were found to have a mean number of FPs/scan ranging from 0.09 to 3.8 and a mean sensitivity (on a nodule basis) ranging from 0.54 to 0.96 [ 28 ]. In a study by Li et al [ 30 ], it was shown that deep learning algorithms not derived only from the LIDC-IDRI dataset [ 31 ] achieved good performance in nodule detection when tested on an external dataset, with sensitivity ranging from 0.75 to 1.00.…”
Section: Discussionmentioning
confidence: 99%
“…Leaving aside clinical considerations that contribute to the differential diagnosis of oral cancer and that the actual gold standard for tumor identification is the biopsy's histopathological analysis by a pathologist, it is important to highlight that AI holds great promise in this manner and is gaining weight in medical areas [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews endorse AI assistance in lung nodule detection, exhibiting accuracy ranging from 82-98% and surpassing radiologists by 7% to 56%particularly in detecting small nodules and among younger radiologists. AI has also contributed to reducing false-positive rates within the last years [25][26][27].…”
Section: Imaging 1402 Artificial Intelligencementioning
confidence: 99%